Testing models in the development of a web platform for the exchange of three-dimensional models - D.A. Makuhovska; M.O. Ukrainets; I.D. Liminovych; D.D. Plechystyy; V.V. Budanov (Технічна інженерія)
The article investigates the models of testing support in the development of a web-based platform for the exchange of three-dimensional models. The purpose of this work is to determine certain approaches to testing that will be effective and allow improving the quality and reliability of a product focused on working with three-dimensional models. To achieve this goal, deterministic and probabilistic models of software reliability are analysed. Deterministic models are used to evaluate the structure and complexity of the code and assess test coverage, which helps to detect certain problems in the software code in a timely manner. In turn, probabilistic models are used to take into account random factors, such as unpredictable errors, and allow predicting the reliability of the platform in real-world conditions. The main focus is on analysing these models in order to determine which ones are best suited to web-based platforms for exchanging 3D-models and ensure reliable product performance. The study found that deterministic models are effective in providing a certain degree of structure and timely detection of certain errors, while probabilistic approaches are better suited to modelling real-world conditions of use. Both methods complement each other, creating a comprehensive approach to testing. The results obtained can be used for development aimed at improving the performance of web platforms to meet modern requirements. This provides a significant contribution to the development of a reliable product, a web resource for working with three-dimensional graphics.